Perlawanan Pedagang Kaki Lima di Laman Boenda Tanjungpinang - Paul Samuelson Sitorus; Sri Wahyuni; Emmy Solina (Sociology Department Of Syiah Kuala University, 2022)
This study aims to describe the resistance carried out by street vendors on the Boenda Tanjung Pinang page. This study uses a qualitative approach, data obtained from interviews and observations. This study identifies that the policing carried out by Satpol PP against street vendors is a form of implementing local government regulations. To get around the policing activities that the Satpol PP is continuously carrying out, street vendors fight in two forms, namely hidden and open resistance. The two forms of resistance became an alternative for traders to continue selling at the Boenda site and to fulfill their daily needs. AbstrakKajian ini bertujuan untuk mendeskripsikan tentang perlawanan yang dilakukan oleh Pedagang Kaki Lima di Laman Boenda Tanjung Pinang. Kajian ini menggunakan pendekatan kualitatif, data diperoleh dari wawancara dan observasi. Kajian ini mengidentifikasi bahwa penertiban yang dilakukan oleh Satpol PP terhadap pedagang kaki lima merupakan bentuk penerapan peraturan pemerintah daerah. Untuk menyiasati kegiatan penertiban yang terus dilakukan oleh Satpol PP, para pedagang kaki lima melakukan perlawanan dalam dua bentuk yaitu perlawanan tersembunyi dan terbuka. Kedua bentuk perlawanan itu menjadi alternatif para pedagang untuk tetap berjualan di lokasi laman Boenda dan untuk memenuhi kebutuhan hidup mereka.